Standardized Laparoscopic Sphincter-preserving Total Mesorectal Excision For Rectal Cancer: Median of 10 Years' Long-term Oncologic Outcome in 217 Unselected Consecutive Patients. Issue 5 (October 2019) - Bademler, Suleyman; Koza, Kadir B.; Ucuncu, Muhammed Z.; Tokmak, Handan; Bakir, Baris; Oral, Ethem N.; Asoglu, Oktar
Abstract : This study was designed to evaluate the impact of a standardized laparoscopic total mesorectal excision (TME) on the long-term oncologic outcome. Unselected consecutive patients with rectal cancer underwent a standardized laparoscopic TME with medial to lateral approach encompassing 9 sequential steps. From 2005 to June 2012, laparoscopic sphincter-preserving TME was attempted in 217 patients. Mean follow-up of all patients was a median of 91 months (range, 3 to 164 mo). The local recurrence rate was 6.5%, and the distant recurrence rate was 19.8%. The 10-year disease-free survival (DFS) rates were 76.4% and overall survival (OS) was 67.1%. In the converted group, DFS and OS were 50% and 46.7%, respectively. In the laparoscopic group, DFS and OS were 78.3% and 68.5%, respectively. A standardized laparoscopic sphincter-preserving TME resulted in a favorable long-term oncologic outcome in unselected patients with rectal cancer. Conversion to open surgery has impaired OS and DFS.